The Effectiveness Of Guiding Block For The Visually Disabled In Malioboro Street, Yogyakarta Indonesia - Hastuti, Mirna (2003)
One of the goals in the planning of modern cities would be to provide comfort, safety and flexibility for people of all ages, sizes and abilities. This concept is known as the Universal Design or Barrier Free Environments. Yogyakarta was the first city in Indonesia that introduced and promoted the Barrier Free Environment through the use of guiding block technique. However, the Malioboro pilot project has not been effectively utilised by the intended users, which are the visually disabled. This study aimed to study the effectiveness of the guiding blocks in Malioboro Street. It attempted to seek ways in which the guiding blocks could be utilised more widely by users, especially the visually disabled. This research used a triangulation technique to obtain the data. It consisted of: a) questionnaire with 150 respondents from 3 groups (50 visually disabled, 50 street vendors and 50 visitors); b) observation, utilising the place mapping centre technique; and c) interview, with 35 informants ( 1 5 visually disabled, 8 street vendors, 8 visitors, 2 members of Non-Governmental Organizations (NGOs), and 2 government officials). In this study, it was been observed that the guiding blocks were not effectively used by the visually disabled. This is due to different groups of users of Malioboro Street that have different perceptions regarding the functions of the guiding blocks on Malioboro Street; the visually disabled are monitored by a few organizations which are less influential, and therefore their rights, needs and requirements are not recognized by others; there is a strong competition for spaces along the street resulting in the visually disabled facilities being ignored; there is a lack of enforcement on the part of the authorities; there is not enough awareness campaign being conducted to instil understanding and respect on the need of the visually disabled to use the guiding blocks; the spaces along the street are not delineated clearly according to different users, and there is a lack of political will to ensure that guiding blocks are effectively utilised. The following recommendations are made to improve the effectiveness of the guiding blocks for the visually disabled. These are: more involvement of all parties such as government, Non-Governmental Organizations (NGOs), community, university students, etc to look into the needs of the visually disabled to use the guiding blocks. These groups can offer ideas to solve problems arising from the use of the guiding blocks; there is also a need to provide complimentary facilities which may include ramps, phone booth, rest places and shelter for the visually disabled to function effectively; there should be a wider and more frequent dissemination of information on the needs of the disabled to use the guiding blocks; and there should be a effective law enforcement to assist the visually disabled to use the blocks.